An Analysis of Pragmatism Study of Conversational Maxim used in “Tangled“a Movie by Nathan Greno - Maya Malinda; Suyadi Suyadi (Universitas Batanghari Jambi, 2019)
This study analyzed about conversation obtained from Tangled movie. The conversation or dialogue of the movie of Tangled that speaker must follow conversational maxims. This study is aimed to describe the most frequently of maxim choice used by the main character in the movie of Tangled. In addition, this study is also discuss types of conversational maxim of Grice (1975) of the writer character used the movie of Tangled. The data found 33 data obtained from Tangled movie. Then the data analyzed by using a descriptive qualitative research method. The usage of the number is used to identify the mostly frequent of the maxim used in this study. The data consist of the maxims are as maxim of quality 10 data , maxim of quantity 12 data, maxim of relation 5 data, maxim of manner 6 data. Those are aimed to cooperative conversation in the social life activity. This study can be concluded that the number of data found is 33 data. The maxim of quantity 12 data is the most frequently used in the dialogue. This shows that in the cooperative conversational in the social life activity is maxim of quantity. So, this study can be aimed that in daily conversation, quantity is very important to be used because this maxim is concerned with the amount of information an utterance conveys.The suggestion to the future researcher who interested in this area of pragmatics.